Fire behavior simulations in Eucalytpus urograndis (Clone H13) crop - Alves, Leandro Jorge de Souza; de Souza, Adilson Pacheco; Casavecchia, Bruno Henrique; Dias, Thaíse Karla Ribeiro; Borella, Daniela Roberta; Ferneda, Brena Geliane; Martim, Charles Campoe (Sociedade & Natureza, 2018)
Fire behavior simulations were carried out by two computer programs “BehavePlus” and “Eucalyptus Fire Safety System” (EMSS) and compared to experimental observations (prescribed burning) in an Eucalyptus urograndis (Clone H13) forest, with 4.5 years-old, in the Sorriso County, Mato Grosso State, during the dry season (May to September) of 2015. Experimental burnings occurred in plots of 3.0 x 20.0 m (width and length), with flat topography and considering the interfaces EF (eucalyptus- native forest), EL (eucalyptus-crops) and EE (center of the field). The fire propagation velocity, fire intensity and flame length were evaluated. BehavePlus overestimated all fire behavior variables, regardless of time of year and environmental interface. The best simulations were obtained with EMSS. Based on the simulations of the fire behavior and the safety of the operation, it is recommended to perform firing in July, considering the sequence of EM-EE-EL interfaces.